The Future of Critical Care: Optimizing Technologies and a Learning Healthcare System to Potentiate a More Humanistic Approach to Critical Care. (15th March 2022) - Meissen, Heather; Gong, Michelle Ng; Wong, An-Kwok Ian; Zimmerman, Jerry J.; Nadkarni, Nalini; Kane-Gil, Sandra L.; Amador-Castaneda, Javier; Bailey, Heatherlee; Brown, Samuel M.; DePriest, Ashley D.; Mary Eche, Ifeoma; Narayan, Mayur; et al.
Abstract : While technological innovations are the invariable crux of speculation about the future of critical care, they cannot replace the clinician at the bedside. This article summarizes the work of the Society of Critical Care Medicine–appointed multiprofessional task for the Future of Critical Care. The Task Force notes that critical care practice will be transformed by novel technologies, integration of artificial intelligence decision support algorithms, and advances in seamless data operationalization across diverse healthcare systems and geographic regions and within federated datasets. Yet, new technologies will be relevant and meaningful only if they improve the very human endeavor of caring for someone who is critically ill.